Unhealthy behaviors associated with mental health disorders: a systematic comparative review of diet quality, sedentary behavior, and cannabis and tobacco use - Johnstad, Petter Grahl (Frontiers in Public Health, 2024)
Background There are well-established literatures documenting the associations between mental disorders and unhealthy behaviors such as poor diet quality, sedentary behavior, and cannabis and tobacco use. Few studies have attempted to understand the respective findings in light of each other, however. Objective The purpose of this review was to assemble comparable data for each behavior-disorder association and assess the associations in terms of their overall strength. The review aimed to include a representative, but not exhaustive, range of studies that would allow for explorative comparisons. Methods Eligible studies were identified via Pubmed searches and citation searching, restricted to publications no older than 2015 written in English. To obtain comparable data, only studies that reported findings as odds ratios were included, and risk of bias related to study samples, behavioral measurement disparities, and control variables was assessed via sensitivity analyses. Findings for each disorder were compared on the basis of different measures of central tendency. Results From 3,682 records, 294 studies were included. The review found evidence of associations between each of the four unhealthy behaviors and psychosis, depression, anxiety, bipolar disorder, attention-deficit/hyperactivity disorder (ADHD), and post-traumatic stress disorder (PTSD), while personality disorder was only investigated in relation to cannabis and tobacco use. In overall comparison, the associations were generally of similar strength, and only the association between cannabis use and personality disorder was exceptional in terms of being significantly stronger than its counterparts across disorders and across behaviors. Analyses of bias risk identified some influence from behavioral measurement disparities and lack of adequate statistical control, but findings were generally robust across a range of sensitivity analyses. Conclusion This explorative and comparative review found that poor diet quality, sedentary behavior, and cannabis and tobacco use are about equally strongly associated with a range of different mental disorders. Given the general nature of these associations, we should probably understand them to reflect a general and shared etiology. However, the findings in this review should be regarded as tentative until confirmed by more comprehensive investigations.